2018
DOI: 10.3390/s18082511
|View full text |Cite
|
Sign up to set email alerts
|

RPC-Based Orthorectification for Satellite Images Using FPGA

Abstract: Conventional rational polynomial coefficients (RPC)-based orthorectification methods are unable to satisfy the demands of timely responses to terrorist attacks and disaster rescue. To accelerate the orthorectification processing speed, we propose an on-board orthorectification method, i.e., a field-programmable gate array (FPGA)-based fixed-point (FP)-RPC orthorectification method. The proposed RPC algorithm is first modified using fixed-point arithmetic. Then, the FP-RPC algorithm is implemented using an FPGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The orthorectification of high-resolution satellite images is widely discussed in the literature [3,4], and several models have been developed for their orientation [5][6][7]. However, the availability of new images and models is always a reason for further research and development in search of increasingly optimized and efficient strategies [8,9]. Some commercial software have implemented rigorous, scientifically accredited models such as the well-known Toutin model [10], making such software [11,12] the reference for the most recently performed experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The orthorectification of high-resolution satellite images is widely discussed in the literature [3,4], and several models have been developed for their orientation [5][6][7]. However, the availability of new images and models is always a reason for further research and development in search of increasingly optimized and efficient strategies [8,9]. Some commercial software have implemented rigorous, scientifically accredited models such as the well-known Toutin model [10], making such software [11,12] the reference for the most recently performed experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The RFM was constructed using the RPCs and Shuttle Radar Topography Mission (SRTM) 90 m DEM. The RFM is usually refined via affine transformation based on some CPs [2]. This is defined as follows:…”
Section: Rpc Correctionmentioning
confidence: 99%
“…For the GF-1/GF-6 images corrected by the RFM, the geometric accuracy of the whole image and the local geometric distortions were analyzed: (1) For many GF-1 and GF-6 images, histograms of the RMSE values were statistically analyzed according to different countries, the results of which were used to evaluate the geometric accuracy of whole image. (2) The local geometric distortions can affect the accuracy of the refined RFM; therefore, eight GF-1 images and eight GF-6 images from different countries and with different geometric accuracies were selected to evaluate the local geometric distortions. For each image, the geometric error value of each CP was calculated; then, a plot of geometric errors and a histogram of geometric error values were obtained.…”
Section: Geometric Accuracy Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The HPC model includes heterogeneous computer network, cloud, field programmable gate array, and cluster-based multi-central processing unit (CPU) and graphics processing unit (GPU) systems [15], [16], [17]. The high-efficiency processing algorithms are explored in remote sensing image with HPC, such as hyperspectral imaging and endmember extraction [18], [19], [20], [21]. They concluded that HPC technology exhibits a significant improvement in efficiency compared to traditional computing methods.…”
Section: Introductionmentioning
confidence: 99%